Alice's adventures in Wonderland - Carroll, Lewis (Puffin classics, 2008)
On an ordinary summer's afternoon, Alice tumbles down a hole and an extraordinary adventure begins. In a strange world with even stranger characters, she meets a rabbit with a pocket watch, and a grinning cat, joins a mad tea-party and plays croquet with the fearsome Queen of Hearts! Lost in this weird and worderful fantasy land, Alice begins to wonder exactly how she'll ever find her way home. . .